Collecting Health Research Data: Comparing Mobile Phone-assisted Personal Interviewing to Paper-and-pen Data Collection. Issue 4 (November 2014) - van Heerden, Alastair C.; Norris, Shane A.; Tollman, Stephen M.; Richter, Linda M.
Mobile phone–assisted personal interviewing (MPAPI) is becoming a more widely used technique to collect survey data. Not having a hard copy paper document to return to when cleaning data raises the question of how data error rates compare with traditional paper surveys and at what cost. One hundred health research interviewers trained to use traditional pen-and-paper (PAP) survey methodology were recruited and randomly assigned to either a PAP or an MPAPI group. After receiving training on the survey instrument, each of the 100 interviewers conducted interviews with the same five interviewees, for a total of 500 interviews. Costs associated with the two survey methods were calculated. Very low error rates were achieved in both PAP and MPAPI, with a total of 381 data errors identified in 21, 500 survey items. Findings suggest that experienced, well-trained interviewers using a short, well-constructed survey can produce very low error rates, independent of survey mode and that the benefits of MPAPI would be magnified as the size and complexity of the study increases.